Characterization of the larval habitat of Culicoides sonorensis (Diptera: Ceratopogonidae) with emphasis on the significance of animal manure and the associated bacterial community - Erram, Dinesh (Kansas State University, 2016)
The larval stages of Culicoides sonorensis Wirth and Jones, a confirmed vector of bluetongue and epizootic hemorrhagic disease viruses affecting ruminants in North America, have been observed to occur typically in animal waste enhanced muds. In this dissertation, I studied the larval development (first instar to adult stage) and oviposition (four-choice assays) of C. sonorensis on sterilized mud (autoclaved) enriched with manure of different farm animal species (dairy cattle, beef cattle, sheep, goats, pigs, horses, white-tailed deer, and chicken). In addition, to determine why only some manure-polluted sites are colonized by C. sonorensis even when they are in close proximity to each other, I examined the moisture levels and microbial concentrations (mud) and physicochemical characteristics (standing water) of a manure-overflow pond site producing C. sonorensis and compared them to nearby cattle stock pond site(s) that produced different Culicoides species. Finally, as the first step in examining the role of microbiome in various physiological functions of C. sonorensis and other suspected/potential vector Culicoides species, I assessed the bacterial communities in field-collected adult females of C. sonorensis, C. crepuscularis, C. haematopotus, and C. stellifer (Illumina sequencing of 16S rRNA gene). In larval development experiments, the proportion of adults emerged and development time to adult stage varied with manure type and its concentration present in the substrate. Mud supplemented with chicken manure did not support C. sonorensis development, mud enriched with white-tailed deer manure poorly supported midge development, while C. sonorensis development in mud enhanced with manure of sheep, goats, beef cattle, dairy cattle, pigs, and horses varied. In oviposition experiments, colonized females preferred to deposit eggs on substrates without animal manure over substrates with animal manure. In subsequent studies, the manure-overflow pond site that produced mainly C. sonorensis contained significantly higher total aerobic culturable bacteria, pH, salinity, total dissolved solids, and conductivity levels than cattle stock pond sites that produced different Culicoides species. Finally, bacterial composition of field-collected C. sonorensis adult females comprised mainly of the phyla Proteobacteria and Firmicutes, while the majority of bacterial taxa identified from C. crepuscularis, C. haematopotus, and C. stellifer belonged to Proteobacteria. An unidentified bacterial genus (related to Tumebacillus), Propionibacterium, and Curvibacter were detected commonly across all four midge species. These results suggest that manure of several farm animal species can contribute to C. sonorensis development in the field. However, oviposition preferences remain uncertain, as colonized females appeared to show aversion to animal manure, which is in contradiction to the typical presence of C. sonorensis larvae in animal waste enhanced muds. Nonetheless, variations in microbial and/or physicochemical conditions in the larval habitats likely play a role in the differential emergence of C. sonorensis from various manure-polluted sites. Moreover, some bacterial taxa are associated commonly with C. sonorensis and other suspected/potential vector Culicoides species. Future studies are needed to examine oviposition preferences of field-collected females, life history traits of adults emerging from various manure-enriched substrates, developmental requirements of larvae, and the role of microbiome in various physiological functions of the host including vector competence for orbiviruses.
Keywords: Culicoides sonorensis; animal manure; larval development; oviposition; bacteria; 16S rRNA gene